Supporting Women Throughout the Coronavirus (COVID-19) Emergency Response and Economic Recovery - World Bank (World Bank, Washington, DC, 2020)
This brief highlight evidence from the Africa gender innovation lab and other promising research on mechanisms that can help protect the lives and livelihoods of women and girls - at the household level, in firms and farms, and during adolescence - in the context of the COVID-19 (Coronavirus) pandemic.